Comparison of methods of rice cultivation in relation to water management practices and sustainability in South-Eastern Rajasthan - Narolia, R.S.; Singh, Pratap; Meena, H.P. (Annals of Agricultural Research, 2014)
On-farm trials were conducted during kharif seasons of 2010 to 2012 under operational research programme of AICRP- water management project, Agricultural Research Station, Kota, Rajasthan to compare the system of rice intensification (SRI) with conventional method and farmers’ practice of rice cultivation. Treatments comprised of SRI, conventional method (irrigation of 5Â±2 cm standing water and refilling at 1-3 days after disappearance of ponding water and farmers practice (continuous submergence). SRI and conventional method of rice cultivation resulted in 37.2 and 7.0 percent higher grain yield (5.53 t/ha and 4.32 t/ha) as compared to farmer’s practice (4.03 t/ha). SRI method was found superior with respect to sustainability yield index (0.937) and sustainability value index (0.923) as compared to conventional and farmers practice. However, conventional method was also found better than FP having higher SYI (0.89) and SVI (0.864). The FP registered lower value of SYI (0.822) and SVI (0.680) and being 7.2, 1.8 and 9.2, 2.2 per cent lower than SRI and conventional method, respectively. SRI technique proved better due to higher irrigation water productivity (30.9 Rs/ m3) and water expanse efficiency (127.2 kg/ha-cm) and resulting incremental benefit cost ratio 7.23 which were followed by conventional practice. Irrigation water productivity (30.9, 18.1 Rs. /m3), water expanse efficiency (127.2, 75.4 kg/ha-cm) and incremental benefit cost ratio (7.23, 7.13) were observed higher in SRI and conventional method than farmers practice.